Exploration of the association of selected pain diagnoses with risky alcohol use among active duty soldiers. Issue 4 (1st October 2020) - Reif, Sharon; Adams, Rachel Sayko; Ritter, Grant A.; Larson, Mary Jo
Abstract: Background: Pain and its consequences remain of concern, particularly in high-risk occupations such as the military. Alcohol is a legal and accessible means of self-medication, and risky alcohol use is associated with potentially serious consequences. This exploratory analysis aimed to better understand the association of selected pain diagnoses with risky alcohol use among soldiers returning from deployment. Methods: Analysis of data from active duty soldiers returning from Afghanistan or Iraq deployments in fiscal years 2008–2011 who completed Department of Defense health questionnaires after deployment ( n  = 267, 100). Each questionnaire included self-reported alcohol consumption and items yielding AUDIT-C screening scores. Military Health System data were used to identify diagnoses of pain-related conditions. Results: About 70% of soldiers had none of the selected pain diagnoses either pre- or post-deployment. 10% had incident pain diagnoses (only post-deployment), 7% had persistent pain diagnoses (both pre- and post-deployment), and 13% had remitted pain diagnoses (only pre-deployment). On the AUDIT-C, 39% screened positive for at-risk drinking and 6% were likely to have severe alcohol problems. Half of the respondents reported any binge drinking; 20% at least monthly binge drinking. Logistic regression analyses found reduced odds of risky alcohol use post-deployment in association with incident and persistent pain diagnoses, compared to no pain diagnoses pre- or post-deployment. Conclusions: Pain diagnoses, binge drinking, and risky alcohol use were prevalent among this sample of Army soldiers. An inverse relationship was found between pain diagnosis (incident, persistent) and risky alcohol use post-deployment. Attention should continue to be paid to risky alcohol use in this population, yet these exploratory findings do not suggest that soldiers with the pain diagnoses used in this study are at greater risk. Combat exposure, traumatic brain injury, and psychological health were more important predictors, and should continue to warrant enhanced alcohol screening.